Kemitraan Strategis dalam Institusi Pendidikan: Integrasi Visi, Misi, dan Nilai Dasar Melalui Kerangka Balanced Scorecard (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Educational institutions are required to implement a management strategy that is more systematic, measurable, and aligned with the organization's long-term direction. This research aims to examine how the integration of the formulation of vision, mission, and basic values into the framework of the Balanced Scorecard can strengthen the management of strategic strategies and partnerships in educational institutions. This study was conducted through a descriptive qualitative approach with systematic literature study methods and institutional documentation analysis, including strategic plans, statutes, and annual reports from various educational institutions. The results of the study show that the integration of vision and mission in each Balanced Scorecard perspective is able to create performance indicators that are directed, consistent, and in accordance with the strategic direction of the institution. Institutional foundational values have proven to play an important role in shaping an organizational culture that supports performance achievement. In addition, partnership strategies can also be improved through performance indicators that measure the effectiveness of external relationships. This research makes an important contribution to the development of value-based education management practices by presenting a framework of integration that can be replicated. These findings suggest the importance of developing vision, mission, and value-based evaluation policies and systems in the management of educational institutions in an era of global collaboration and competition.